"Diabetes care at doorsteps": A customised mobile van for the prevention, screening, detection and management of diabetes in the urban underprivileged populations of Delhi. Issue 6 (November 2019) - Gopalan, Hema S; Haque, Intazaamul; Ahmad, Shamshad; Gaur, Ashok; Misra, Anoop
Abstract: Diabetes is on the rise in India and recently shown to be increasing in the urban underprivileged. Lack of awareness of the disease, its complications, combined with lack of financial resources among the underprivileged, often results in late detection and more complications in them. To combat this, healthcare delivered at the doorstep through the use of a customised mobile medical van is a potentially attractive option. We used a customized mobile van (included trained personnel, glucose meters, fundus evaluation camera, apparatus for detection of neuropathy and foot circulation and net enabled Skype calling for remote consultation) for educating general population regarding healthy lifestyle and screening, management and intervention in patients with diabetes. The project covered 10 underprivileged areas (n, 2, 31, 000 people) in Delhi. Total of 24, 072 individuals (10.9% of total population) attended 352 awareness sessions. A total 3, 12, 347 visits (included repeat visits) were carried out for screening, education and management for obesity and diabetes. During screening (n, 16, 834), 2933 subjects (18.7%) had high random blood glucose levels (>200 mg/dL) and had a blood pressure averaging 127.1 ± 23.6/81.3 ± 16.6 mm of mercury (n, 16, 339). A pre-post intensive lifestyle counselling for 6 months in a subset of 352 diabetic patients (of which 77.8% i.e. n, 274 were overweight/obese) showed a significant lowering in weight (p < 0.001). In addition, 292 frontline workers and 256 paramedical workers were given training regarding lifestyle and diabetes, over 20 sessions. Based on achievements of this project of spreading awareness, screening, and management of diabetes and obesity in the large number of individuals in urban underprivileged colony, we believe this project could be extended to other cities and rural areas of India, and to other developing countries as well.